Quantifying dissolved black carbon in fire-affected estuaries: a case study from the 2019–2020 Australian bushfires - Laicher-Edwards, Dylan; Liu, Lei; Benkendorff, Kirsten; Johnston, Scott G.; Ferguson, Angus; Reithmaier, Gloria M. S.; Borrow, Renee; Maher, Damien T. (Frontiers in Water, 2026)
Changing fire regimes, marked by more intense, extensive, and catastrophic wildfires are predicted to lead to significant shifts in carbon cycling along the land-ocean-aquatic-continuum (LOAC). One important consequence of bushfires is the mobilisation of dissolved black carbon (DBC), which can be released from soils overtime into downstream waters. Estuaries, which reside at the critical terrestrial-ocean interface, remain poorly studied in this context, despite their key role in processing and transporting organic matter. This study examined six intermittently closed and open lake or lagoons (ICOLLs) on the south coast of New South Wales, Australia, which were affected by the 2019–2020 bushfires. Surface water and shallow groundwater samples were analysed for dissolved organic carbon (DOC) and DBC concentrations using the benzenepolycarboxylic acid (BPCA) method. DBC concentrations ranged from 2.33 to 77.80 μmol L−1, with higher levels generally observed in shallow groundwater samples, and results demonstrated a strong correlation between DOC and DBC concentrations. Findings suggest that both sources and transport pathways are linked, and that estuaries may significantly attenuate dissolved black carbon before it reaches the ocean. Results highlight the estuary-specific nature of post-fire carbon dynamics and emphasize the urgent need for baseline data to better understand how increasingly severe fire regimes impact water quality and carbon cycling in coastal systems.